Statecraft, Welfare and the Politics of Inclusion - Jayasuriya, K. author. aut Link
X, 192 p.
Keywords: Jayasuriya explores the dynamics of a new social agenda conceived within the boundaries of neo liberalism. The enhanced focus on issues such as poverty through strategies of inclusion frames new terms of engagement for social policy, different from that which existed in the terrain of the post war welfare state.